2022
DOI: 10.1136/jitc-2022-005158
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cetuximab plus PD-1 inhibitor differs by HPV status in head and neck squamous cell carcinoma: a systematic review and meta-analysis

Abstract: BackgroundThe addition of cetuximab significantly increased the antitumor effect of programmed cell death protein 1 (PD-1) inhibitors in recurrent or metastatic head and neck squamous cell carcinoma (HNSCC). However, preliminary analyses suggested that human papillomavirus (HPV)-positive disease benefited less than HPV-negative disease. Therefore, we conducted a meta-analysis to assess whether the efficacy of the combination therapy varied according to HPV status in HNSCC.MethodsWe identified clinical trials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“… 27 , 37 , 38 Examples of such immune-suppressive loops include activation of PD-1 expression on immune cells, activation of PD-L1 expression on tumor cells through direct EGFR signaling and indirect interferon/STAT-1 pathway stimulation, and the intra-tumoral increase in the regulatory T (Treg) cells expressing CTLA-4 or PD-L1, known as one of the most immune-suppressive mechanisms. 29 , 46 48 Cetuximab is also known for its immune-stimulatory effects. Activation of both the innate and adaptive immune systems stimulates dendritic cells, macrophages, and other immune cells, which leads to the recruitment and priming of effector T cells in the TME.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 , 37 , 38 Examples of such immune-suppressive loops include activation of PD-1 expression on immune cells, activation of PD-L1 expression on tumor cells through direct EGFR signaling and indirect interferon/STAT-1 pathway stimulation, and the intra-tumoral increase in the regulatory T (Treg) cells expressing CTLA-4 or PD-L1, known as one of the most immune-suppressive mechanisms. 29 , 46 48 Cetuximab is also known for its immune-stimulatory effects. Activation of both the innate and adaptive immune systems stimulates dendritic cells, macrophages, and other immune cells, which leads to the recruitment and priming of effector T cells in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the advanced R/M HNSCC tumors are dominated by an immune-suppressive TME with increased Tregs, immune-inhibitory M2 macrophages, myeloid-derived suppressive cells, and immune-inhibitory cytokines and growth factors or by TME with low immune infiltrate referred to as a ‘cold immune phenotype’. 47 51 Patients with ‘hot’ TME, with high levels of CD8 T cells and NK cells, have improved response to ICIs and improved prognosis independent of HPV status. 53 , 54 Substantial research efforts have explored strategies to capitalize upon a ‘hot immune phenotype’ and to convert their ‘cold’ and immune-suppressive counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two major Phase 3 trials found cetuximab to be inferior to standard cisplatin treatment in combination with radiotherapy for HPV + OPSCC [ 185 , 186 ]. A recent meta-analysis further revealed that the combination of cetuximab and a PD-1 inhibitor improved the OS rate of HPV − OPSCC only compared to PD-1 inhibitor monotherapy, while patients with HPV + OPSCC did not experience the same benefit [ 187 ]. Another Phase 3 trial investigated adding panitumumab, another anti-EGFR monoclonal antibody, to chemotherapy and found improved OS only in HPV − OPSCC [ 188 ].…”
Section: Emerging Therapeutic Strategiesmentioning
confidence: 99%
“…Another potentially promising investigation could be combining ficlatuzumab, cetuximab, and PD-1 ICB, given the clinical synergy recently described between PD-1 inhibitor nivolumab and cetuximab in R/M HPV − HNSCC. 38,39 It may also be interesting to test an EGFR-MET–bispecific antibody such as amivantamab as described in patients with lung cancer in a phase I clinical trial. 40 Finally, RNA expression and/or proteomic analyses of HNSCC from patients or in experimental preclinical models may inform changes in pathways induced by this combination and therefore may identify additional targets of interest—the paradigm of personalized medicine.…”
mentioning
confidence: 99%